Studies on Schismatoglottideae (Araceae) of Borneo XX: Beccari's «La Più piccola delle Aracee» (Microcasia pygmaea) recollected and transferred to Bucephalandra Schott - Boyce, P.C; Wong Sin, Yeng (Taylor & Francis Ltd., 2012)
Beccari's Microcasia pygmaea has been recollected in Sarawak after almost 145 years. Examination reveals, contrary to recent taxonomic treatments, it to be a distinct species (of the genus Bucephalandra) not conspecific with Bucephalandra motleyana Schott. Microcasia pygmaea Becc. is here transferred to Bucephalandra as Bucephalandra pygmaea (Becc.) P.C. Boyce & S.Y. Wong, comb. nov. Notes on taxonomically critical morphologies are provided. Bucephalandra is now considered to comprise five published accepted species, elucidated in a new key. Notes on the taxonomy of Bucephalandra and Microcasia are given and Bucephalandra pygmaea is illustrated from living plants.